An optimised age-based dosing regimen for single low-dose primaquine for blocking malaria transmission in Cambodia. Issue 1 (December 2016) - Leang, Rithea; Khu, Naw; Mukaka, Mavuto; Debackere, Mark; Tripura, Rupam; Kheang, Soy; Chy, Say; Kak, Neeraj; Buchy, Philippe; Tarantola, Arnaud; Menard, Didier; Roca-Felterer, Arantxa; et al.
Abstract Background In 2012, the World Health Organization recommended the addition of single low-dose primaquine (SLDPQ, 0.25 mg base/kg body weight) to artemisinin combination therapies to block the transmission ofPlasmodium falciparum without testing for glucose-6-phosphate dehydrogenase deficiency. The targeted group was non-pregnant patients aged ≥ 1 year (later changed to ≥ 6 months) with acute uncomplicated falciparum malaria, primarily in countries with artemisinin-resistantP. falciparum (ARPf). No dosing regimen was suggested, leaving malaria control programmes and clinicians in limbo. Therefore, we designed a user-friendly, age-based SLDPQ regimen for Cambodia, the country most affected by ARPf. Methods By reviewing primaquine's pharmacology, we defined a therapeutic dose range of 0.15–0.38 mg base/kg (9–22.5 mg in a 60-kg adult) for a therapeutic index of 2.5. Primaquine doses (1–20 mg) were tested using a modelled, anthropometric database of 28, 138 Cambodian individuals (22, 772 healthy, 4119 with malaria and 1247 with other infections); age distributions were: 0.5–4 years (20.0 %, n = 5640), 5–12 years (9.1 %, n = 2559), 13–17 years (9.1 %, n = 2550), and ≥ 18 years (61.8 %, n = 17, 389). Optimal age-dosing groups were selected according to calculated mg base/kg doses and proportions of individuals receiving a therapeutic dose. Results Four age-dosing bands were defined: (1) 0.5–4 years, (2) 5–9 years, (3) 10–14 years, and (4) ≥15 years to receive 2.5, 5, 7.5, and 15 mg of primaquine base, resulting in therapeutic doses in 97.4 % (5494/5640), 90.5 % (1511/1669), 97.7 % (1473/1508), and 95.7 % (18, 489/19, 321) of individuals, respectively. Corresponding median (1st–99th centiles) mg base/kg doses of primaquine were (1) 0.23 (0.15–0.38), (2) 0.29 (0.18–0.45), (3) 0.27 (0.15–0.39), and (4) 0.29 (0.20–0.42). Conclusions This age-based SLDPQ regimen could contribute substantially to malaria elimination and requires urgent evaluation in Cambodia and other countries with similar anthropometric characteristics. It guides primaquine manufacturers on suitable tablet strengths and doses for paediatric-friendly formulations. Development of similar age-based dosing recommendations for Africa is needed.